(3cJGH fSje GdSMQs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg fSje GdSMQ Ydi cHO GdcQhH hJQjGb Se Gdgehe s
(3BNQgG (B:s
(3ai JbSje HjhJ GdYQH hJaUjdgG hhGbjg ef MLQ Je cJGH fSje GdSMQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg fbhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs